The effects of fake reviews during stepwise topic movement on shopping attitude in social network marketing - Masoumeh Hosseinzadeh Shahri; Farideh Haghbin; Yousef Qaseminezhad Raeini; Narjes Monfared (MethodsX, 2023)
Although the influence of consumer reviews is increasing in weight, far-flung consumer comments on social networks are a retrogressive problem, disturbing users' attention in reviews studies by interpreting them as misleading messages. The need for investigating the unknown meaning layers of fake reviews in the stepwise topic movement of conversations and examining the effects of the fake reviews on consumers’ shopping attitudes encouraged us to adopt an integrated approach to marketing and discourse analyses. • Qualitative analysis: To qualitatively investigate the stepwise topic movement of fake reviews in each sampled conversation of the research, three phases were taken into consideration: firstly, identification of topic opening; then, topic closing procedure; and finally, the topic switch toward topic drift. • Quantitative investigation: we develop a questionnaire using multidisciplinary research variables. Then, the reliability and validity of the questionnaire were assessed using Cronbach's alpha and convergent and discriminant values, respectively. After that, the questionnaire was evaluated among a research sample. The data was analysed based on structural equation modeling (SEM) and machine learning (ML). • Conclusion: It was found that fake reviews using topic coherence and grammatical-lexical cohesion mechanisms had positive effects on shopping attitudes. Moreover, fake reviews using topic drift mechanisms influenced consumers’ shopping attitudes.